First Report of Hb Limassol [β8(A5)Lys→Asn; HBB: c.27G>C] from Odisha, India. (1st November 2016) - Meher, Satyabrata; Dehury, Snehadhini; Jana, Arpita; Bhattacharya, Subhra; Patel, Amrita; Das, Kishalaya; Patel, Siris; Sarkar, Biswanath; Mohanty, Pradeep Kumar
Abstract: In this short report, we describe the clinical presentation of a rare hemoglobin (Hb) variant, Hb Limassol [β8(A5)Lys→Asn; HBB : c.27G>C] with a faster electrophoretic mobility than Hb A and that elutes in the P3 window on cation exchange high performance liquid chromatography (HPLC). This sequence variation at codon 8 (AA G >AA C ) of the HBB gene was found in the four heterozygous cases, all of whom were clinically asymptomatic.